Plasmin inhibitor deficiency: A case report - Aissaoui, Ouissal (Clin Case Rep, 2020)
Plasmin inhibitor deficiency is an overlooked cause of hemorrhage. It is a rare disease. Delayed post‐traumatic occurrence of bleeding is an essential feature. The specific dosage must be performed to diagnose cases of severe, persistent bleeding, contrasting with normal usual tests of hemostasis.